Peningkatan Pemahaman Nasabah melalui Penerapan Akad Wadi’ah pada Bank Madani Syari’ah - Lailatul Fitri; Yenie Eva Damayanti (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2023)
This service focuses on implementing wadiah contracts at Bank Madani Syariah. The purpose of this service is to find out what the implementation of the wadiah contract is like at Bank Madani Syariah. In this service using descriptive qualitative research methods. The object of this research uses secondary data data originating from literature studies such as books, journals, articles, and so on. Data collection techniques are observation, interviews, and documentation. The results of the study show: 1) The implementation of the wadiah contract at Bank Madani Syariah uses the wadiah yad dhammanah contract which means safekeeping of goods/money where the recipient of the deposit with or without permission of the owner of the goods/money can take advantage of the deposit and must be responsible for loss or damage to the goods or deposited money. 2) And in wadiah yad dhammanah contract savings, use a profit sharing deposit scheme.